The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1186/s13020-017-0154-9
|View full text |Cite
|
Sign up to set email alerts
|

Active fraction (HS7) from Taiwanofungus camphoratus inhibits AKT-mTOR, ERK and STAT3 pathways and induces CDK inhibitors in CL1-0 human lung cancer cells

Abstract: BackgroundThe non-small cell lung cancer (NSCLC) is the leading cause of cancer death worldwide. In NSCLC, the oncogenic AKT-mTOR, ERK and STAT3 pathways are commonly dysregulated and have emerged as attractive targets for therapeutic developments. In a relatively limited subset of NSCLC, these pathways driven by mutant EGFR can be treated by the tyrosine kinase inhibitors (TKIs)-mediated targeted therapy. However, for the most NSCLC, more novel targeted agents are imperatively needed. Therefore, we investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…Fungal products display widespread biological activities such as anti-inflammation, anti-cancer, and immunomodulatory effects, and thus these species represent a wealth of functional foods and drug precursors [ 8 , 9 ]. Mounting evidence suggests that fungal extracts might protect against certain types of cancers, especially lung adenocarcinoma [ 10 , 11 ]. Among them, fungal immunomodulatory proteins (FIPs), which are widely found in fungi, have well-known, strong inhibitory effects on lung adenocarcinoma.…”
Section: Introductionmentioning
confidence: 99%
“…Fungal products display widespread biological activities such as anti-inflammation, anti-cancer, and immunomodulatory effects, and thus these species represent a wealth of functional foods and drug precursors [ 8 , 9 ]. Mounting evidence suggests that fungal extracts might protect against certain types of cancers, especially lung adenocarcinoma [ 10 , 11 ]. Among them, fungal immunomodulatory proteins (FIPs), which are widely found in fungi, have well-known, strong inhibitory effects on lung adenocarcinoma.…”
Section: Introductionmentioning
confidence: 99%
“…In UC patients, the severity of the intestinal lesion was positively correlated with the expression of STAT3 [22]. To further elucidate the effect of HJD on JAK2/STAT3 pathway, AG490, a specific JAK2 inhibitor, was used to block the JAK2/STAT3 pathway [24]. We found that, similar to that reported about the overexpression of STAT3 and NF-KB caused abnormal activation of JAK2/STAT3 pathway [25], the expressions of JAK2 and STAT3 in the UC group were significantly increased.…”
Section: Discussionmentioning
confidence: 99%
“…Western blotting assay was performed according to previous studies [ 34 ]. Briefly, exponentially growing cells were seeded in culture dish (100 mm) at a density of 2 × 10 6 /dish and allowed to attach overnight.…”
Section: Methodsmentioning
confidence: 99%